The relationship between central bank independence and systemic fragility: global evidence - Duc Nguyen Nguyen; Thuy T. Dang (Cogent Economics & Finance, 2022)
This study investigates the relationship between central bank independence and financial stability in a global sample covering 56 countries from 1980 to 2012. We find strong and robust evidence that central bank independence and its four dimensions (personnel independence, financial independence, policy independence, and central bank objectives) are negatively associated with bank systemic risk. In addition, the results indicate that the reductive effect of central bank independence on systemic risk is more pronounced during actual episodes of banking crises. Moreover, our results suggest that the democratic environment plays a vital role in moderating the central bank independence - systemic risk nexus.
Keywords: G21; E58; 330; central bank independence; systemic risk; democracy